Pedagogi Yesus Dalam Perspektif Progresifisme Pendidikan - Yakobus Ndona; Liber Siagian; Sampitmo Habeahan (Jurnal Christian Humaniora, 2021)
AbstractJesus Christ is not only a founder of Christianity. Jesus is from pedagogical perspective including an educational figures with the power of charisma who until now has influenced to the world of Christianity. The charisma pedagogy of Jesus appears in authoritative teaching, the charismatic, delivery of messianic expectations and a distinctive educational pattern. A study of a gospels, reveals that the pedagogy of Jesus was not oriented toward the inculcation of religious laws as done by the Jewish rabbis. Jesus education focused on renewing the heart based on the value of the kingdom of God.  Jesus did not build a formal class but made Himself and the environment around Him as a learning laboratory. This pattern shows that the pedagogy of Jesus has both parallel and contradiction with the various educational which developing in the world of education. This paper examines the richness of Jesus pedagogy as seem from a progressivism perspective of an education. The philosophical hermeneutic analysis found the substance, pattern and objective value of Jesus education. Then, through reflection and heuristics, we find contextual values that have implications for the world of Christian education and is an inspiration for educational activists today.Key words : Jesus, Pedagogy, Progressivism  AbstrakYesus Kristus tidak hanya seorang pendiri kristianitas. Yesus, dari perspektif pedagogik  termasuk tokoh pendidikan dengan kekuatan kharisma yang sampai sekarang berpengaruh pada dunia kekristenan. Kharisma pedagogi Yesus tampak dalam pengajaran yang otoritatif, berkharisma, penyampaian harapan-harapan mesianik, dan pola pendidikan yang khas. Telah terhadap kitab-kitab Injil memperlihatkan bahwa pedagogi Yesus tidak berorientasi pada penanaman hukum-hukum agama seperti yang dilakukan para rabi Yahudi. Pendidikan Yesus terfokus pada pembaharuan hati yang berlandaskan pada nilai-nilai kerajaan Allah. Yesus tidak membangun kelas-kelas formal, tetapi menjadikan diri-Nya dan lingkungan sekitar sebagai laboratorium belajar. Pola ini memperlihatkan bahwa pedagogi Yesus memiliki paralel sekaligus kontradiksi dengan berbagai aliran pendidikan yang sekarang berkembang dalam dunia pendidikan. Tulisan ini mengkaji kekayaan pedagogi Yesus yang dilihat dari perspektif progresifisme pendidikan.Analisa hermeneutika falsafati menemukan substansi,  pola dan nilai objektif pendidikan Yesus, kemudian lewat gerak refleksi dan heuristika menemukan nilai kontektual yang berimplikasi bagi dunia pendidikan Kristen, dan inspirasi bagi para penggiat pendidikan dewasa ini. Kata kunci: Pedagogi, Progresifisme, Yesus,